2004
DOI: 10.1002/pmic.200300556
|View full text |Cite
|
Sign up to set email alerts
|

Screening for N‐glycosylated proteins by liquid chromatography mass spectrometry

Abstract: In the last few years mass spectrometry has become the method of choice for characterization of post-translationally modified proteins. Whereas most protein chemical modifications are binary in the sense that only one change can be associated with a given residue, many different oligosaccharides can be attached to a glycosylation site residue. The detailed characterization of glycoproteins in complex biological samples is extremely challenging. However, information on N-glycosylation can be gained at an interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
171
2
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(177 citation statements)
references
References 31 publications
3
171
2
1
Order By: Relevance
“…Using the urological 2-DE databases, pathologic subtypes of solid bladder tumor tissue specimens could be distinguished on the basis of protein fingerprints. 12,20,21 Although a number of dysregulated proteins have been identified in a variety of tissue-based studies, it is disappointing that no reliable markers have been identified for transitional cell carcinoma, the most common type of bladder cancer. Through the proteomic study of a set of only six urine samples, Kageyama et al 22 were able to identify a potential tumor marker, calreticulin, which is found in the urine of patients with bladder carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Using the urological 2-DE databases, pathologic subtypes of solid bladder tumor tissue specimens could be distinguished on the basis of protein fingerprints. 12,20,21 Although a number of dysregulated proteins have been identified in a variety of tissue-based studies, it is disappointing that no reliable markers have been identified for transitional cell carcinoma, the most common type of bladder cancer. Through the proteomic study of a set of only six urine samples, Kageyama et al 22 were able to identify a potential tumor marker, calreticulin, which is found in the urine of patients with bladder carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The use of LAC for isolating both intact glycoproteins and glycopeptides (after proteolytic digestion) can further enhance the identification of glycoproteins. Using these affinity capturing steps and LC-MS/MS, a total of 86 Nglycosylation sites in 77 proteins in human serum were identified [70]. SEC was also found useful for significant enrichment of N-linked glycopeptides relative to nonglycosylated peptides because the N-linked glycans expressed on tryptic glycopeptides contribute substantially to their mass [71].…”
Section: Glycoproteins and Lipoproteinsmentioning
confidence: 99%
“…Lectin affinity chromatography (LAC) is often used for enrichment of either glycoproteins or glycopeptides prior to MS analysis [67][68][69][70]. The use of multilectin affinity column maximized the capturing of glycoproteins and therefore yielded a significant list of 150 glycoproteins in serum/plasma.…”
Section: Glycoproteins and Lipoproteinsmentioning
confidence: 99%
“…94 proteins were identified in previous urine proteome studies (1)(2)(3)(4)(5). 43 proteins were also identified in serum Nglycoproteome (11)(12)(13). 150 were annotated as glycoproteins or subunits of glycoproteins in Swiss-Prot, and 43 were annotated as potential glycoproteins predicted by NetNGlyc 1.0.…”
mentioning
confidence: 99%